(untitled) (Research, Society and Development, 2020)
This study quantified crude protein (CP) requirements for maintenance and gain in female Japanese quail from 1-35 d, using a factorial approach combined with the comparative slaughter technique. A total of 655 quail were evaluated in two phases: starter (1-14 d) and grower (15-35 d). For maintenance, caged birds received 100, 75, 50, or 25% of ad libitum intake; for gain, reference and sequential slaughters were performed. Recorded variables included feed intake, CP intake (CPI), fasted carcass weight (FCW), carcass protein (CPc), protein in carcass dry matter (CPDM), and retained crude protein (CPret). The maintenance CP requirement (CPm) was estimated by linear regressions of CPret on CPI and expressed per metabolic body weight (BW0.67). In the starter phase, CPm = 2.095 g.kg-0.67.d-1 and the efficiency of CP use for gain (k) was 33.4%; in the grower phase, CPm = 6.30 g.kg-0.67.d-1 with k = 34.77%. The net protein requirement for gain was 0.284 and 0.310 g.g-1.d-1, yielding dietary CPg requirements per unit of weight gain of 0.851 and 0.894 g.g-1.d-1 for starter and grower, respectively. For context from the companion energy analysis, the prediction equations were: Starter PB (g.quail−1.d−1) = 2.095 × BW0.67 + 0.851 × WG; Grower – PB (g.quail−1.d−1) = 6.30 × BW0.67 + 0.894 × WG; where BW is live body weight (kg) and WG is daily weight gain (g.quail−1.d−1). Mean ambient temperature was 24.05°C (max 35.2°C), indicating environmental effects on maintenance requirements.